Human history and deep time in nineteenth-century British sciences: An introduction. (June 2015) - Sera-Shriar, Efram
Abstract: The historicisation of humans was a major endeavour in nineteenth-century Britain, and one that led to wide-ranging debates involving a variety of disciplinary approaches, new and old. Within the context of science and medicine these discussions centred on the issues of human origins and evolution. Did the various races living throughout the world develop from a single location, or were their physical and social differences evidence for their separate genesis? Which disciplinary tradition offered the best method for tracing human development? Was it even possible to trace that development, or had too much time passed since the dawn of humans? Furthermore, who had the authority to speak about these matters? This special issue will examine these core questions and introduce some of the ways that researchers attempted to historicise humans within the context of nineteenth-century British sciences.